Insertion and deletion mutagenesis of the human cytomegalovirus genome. - Spaete, R R (1987)
Studies on human cytomegalovirus (CMV) have been limited by a paucity of molecular genetic techniques available for manipulating the viral genome. We have developed methods for site-specific insertion and deletion mutagenesis of CMV utilizing a modified Escherichia coli lacZ gene as a genetic marker. The lacZ gene was placed under the control of the major beta gene regulatory signals and inserted into the viral genome by homologous recombination, disrupting one of two copies of this beta gene within the L-component repeats of CMV DNA. We observed high-level expression of beta-galactosidase by the recombinant in a temporally authentic manner, with levels of this enzyme approaching 1% of total protein in infected cells. Thus, CMV is an efficient vector for high-level expression of foreign gene products in human cells. Using back selection of lacZ-deficient virus in the presence of the chromogenic substrate 5-bromo-4-chloro-3-indolyl beta-D-galactoside, we generated random endpoint deletion mutants. Analysis of these mutants revealed that CMV DNA sequences flanking the insert had been removed, thereby establishing this approach as a means of determining whether sequences flanking a lacZ insertion are dispensable for viral growth. In an initial test of the methods, we have shown that 7800 base pairs of one copy of L-component repeat sequences can be deleted without affecting viral growth in human fibroblasts.